Effects of exercise intervention on body morphology in obese college students: a systematic review and meta-analysis - Liao, Wengao; Yu, Wenlu; Zhao, Yuanji; Ma, Zonglin; Xie, Jie (Frontiers in Public Health, 2025)
BackgroundObesity, as a public health disease, is prevalent among college students and seriously affects their quality of life and academic performance. Timely intervention through an effective exercise program is of great significance in improving the physical health status of obese college students and preventing the emergence of obesity complications. Due to the lack of a systematic review of the effects of exercise intervention on the body shape of obese college students, this study aims to systematically evaluate the effects of exercise intervention on the body shape of obese college students, to provide a reference for the development of an effective exercise intervention program for the group of obese college students.MethodsFive databases, Web of Science, PubMed, Embase, MEDLINE, and The Cochrane Library, were searched for randomized controlled trials (RCTs) on the effects of exercise interventions on obese college student populations from the date of establishment. The methodological quality of the included literature was assessed using the Rob 2.0 risk of bias tool, and then meta-analysis, subgroup analysis, and sensitivity analysis were performed using Review Manager software version 5.4.ResultsA total of 12 original studies with a sample size of 961 individuals were included in this study. Meta-analysis showed that exercise intervention had a statistically significant effect on obese college students’ BMI [SMD = −0.42, 95% CI (−0.80, −0.04), p = 0.03], waist circumference [SMD = −0.61, 95% CI (−1.04, −0.18), p = 0.005] and hip circumference [SMD = −0.72, 95% CI (−1.40, −0.04), p = 0.04], and may be limited by factors such as intervention period, intervention duration, number of interventions, and type of interventions, Exercise interventions had a statistically significant effect on obese college students’ body fat percentage [SMD = −0.33, 95% CI (−0.79, 0.13), p = 0.16] and waist-to-hip ratio [SMD = −0.34, 95% CI (−0.89, 0.22), p = 0.23] did not have a significant intervention effect. Subgroup analyses showed that overall the intervention effect of ≥12 weeks was better than 8 weeks; the intervention effect of 30–60 min/revision was better than <30 min/revision and >60 min/revision; the intervention effect of exercise <5 times per week was better than ≥5 times per week; and the intervention effect of exercise in combination with aerobic combined with resistance training and integrative training was better than that of performing aerobic exercise alone.ConclusionExercise interventions have a positive effect on weight loss and improved body shape in obese college students.Systematic review registrationPROSPERO, CRD420251012259, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251012259.